2022
DOI: 10.1186/s40729-022-00448-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of concentrated growth factors membrane for sealing the socket in alveolar ridge preservation: a randomized controlled trial

Abstract: The purpose of this study was to evaluate the efficacy of concentrated growth factor (CGF) membrane for the sealing of alveolar socket in alveolar ridge preservation (ARP). A total of 22 patients with 24 alveolar sockets were recruited and divided randomly into CGF group and Bio-Gide collagen membrane group. The soft tissue wound healing rate was calculated using intraoral scanner at 3, 7, and 14 days after ARP, and the bone resorption volume at 1, 3, and 5 mm below the alveolar ridge was measured by CBCT at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Five studies [ 45 , 51 , 58 , 60 , 61 ] evaluated the efficacy of CGF in ARP procedures (Table 3 ). Follow-up periods ranged from 3 months to 8 months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies [ 45 , 51 , 58 , 60 , 61 ] evaluated the efficacy of CGF in ARP procedures (Table 3 ). Follow-up periods ranged from 3 months to 8 months.…”
Section: Resultsmentioning
confidence: 99%
“…The other two studies [ 60 , 61 ] compared the effects of collagen membranes with CGF membrane as a barrier membrane. Liu et al [ 61 ] reported that the application of CGF membrane had a faster rate of soft tissue healing and similar bone formation compared with Bio-Gide® collagen membranes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1 ] Following the removal of all teeth in an adult, alveolar process atrophy and hard-tissue reduction occur. [ 2 3 ] The bundle bone at the site loses function and eventually disappears. [ 4 5 6 ] Most bone loss occurs in the horizontal dimension, primarily on the alveolar ridge’s facial aspect.…”
Section: Introductionmentioning
confidence: 99%